Influence of liquid coverage on the anticancer effects of a helium plasma jet on 3D tumor spheroids. Issue 7 (26th February 2020) - Zhang, Jishen; Liu, Dingxin; Zhang, Hao; Xia, Wenjie; Liu, Yifan; Sun, Bowen; Xu, Dehui; Guo, Li; Kong, Michael G.
Abstract: In clinical treatment, the presence or absence of transudate coverage of exposed tumor tissue may have a significant impact on the therapeutic effect of cold atmospheric plasma. Here, the anticancer effects of a plasma jet on three‐dimensional multicellular tumor spheroids with or without liquid coverage were examined. It was found that cell viability decreased more rapidly without liquid coverage than with liquid coverage. Apoptotic cells and reactive oxygen species (ROS) were mainly distributed in the areas of the spheroids directly irradiated by the plasma jet without liquid coverage. However, with liquid coverage, they were distributed throughout the outermost layers of the whole spheroids. Importantly, liquid can help ROS penetrate into spheroids and prolong the anticancer effects of plasma. Abstract : A three‐dimensional multicellular tumor spheroid model was used to study the influence of liquid coverage on the anticancer effects of a helium plasma jet in vivo . The results showed that the distributions of apoptotic cells and reactive oxygen species in the spheroids with or without liquid coverage were very different. Further studies showed that liquid could prevent the physical damage caused by the plasma and prolong the anticancer effects of the plasma jet.